Reconstitution of bacterial autotransporter assembly using purified components - Roman-Hernandez, Giselle (eLife Sciences Publications, Ltd, 2014)
Autotransporters are a superfamily of bacterial virulence factors consisting of an N-terminal extracellular (‘passenger’) domain and a C-terminal β barrel (‘β’) domain that resides in the outer membrane (OM). The mechanism by which the passenger domain is secreted is poorly understood. Here we show that a conserved OM protein insertase (the Bam complex) and a molecular chaperone (SurA) are both necessary and sufficient to promote the complete assembly of the Escherichia coli O157:H7 autotransporter EspP in vitro. Our results indicate that the membrane integration of the β domain is the rate-limiting step in autotransporter assembly and that passenger domain translocation does not require the input of external energy. Furthermore, experiments using nanodiscs strongly suggest that autotransporter assembly is catalyzed by a single copy of the Bam complex. Finally, we describe a method to purify a highly active form of the Bam complex that should facilitate the elucidation of its function. DOI: http://dx.doi.org/10.7554/eLife.04234.001